2011
DOI: 10.1007/s10734-011-9414-2
|View full text |Cite
|
Sign up to set email alerts
|

Different research markets: a disciplinary perspective

Abstract: Drawing upon the notions of academic capitalism and the transformation of academic research from traditional academic orientation into market orientation, the paper sets out to empirically scrutinize the changing nature of academic research, focusing especially on disciplinary differences. The paper is based on a survey of heads of departments and research units at Finnish universities representing all disciplinary groups (n = 255) and on in-depth interviews with Finnish academics (n = 31) in the fields of hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
79
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(89 citation statements)
references
References 20 publications
(22 reference statements)
8
79
0
1
Order By: Relevance
“…It also supports earlier work claiming that traditional academic orientations remain strong in universities, even in periods of decreased core funding and increased pressure for various forms of societal engagement (Ylijoki et al 2011). We still do not have sufficient evidence to conclude whether the frequent ''hybrid profiles'' of academics High Educ (2015) 70:689-709 703 are productive and meaningful or whether they to a greater extent represent incommensurable activities leading to stress and insecurity (c.f.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…It also supports earlier work claiming that traditional academic orientations remain strong in universities, even in periods of decreased core funding and increased pressure for various forms of societal engagement (Ylijoki et al 2011). We still do not have sufficient evidence to conclude whether the frequent ''hybrid profiles'' of academics High Educ (2015) 70:689-709 703 are productive and meaningful or whether they to a greater extent represent incommensurable activities leading to stress and insecurity (c.f.…”
Section: Discussionsupporting
confidence: 69%
“…A large-scale Finnish investigation found that an ''academic orientation'' with strong emphasis on basic research remains central across disciplinary fields (Ylijoki et al 2011). The authors question the thesis that a significant transformation is taking place in universities, arguing instead that academics find different ways to combine an academic orientation with various forms of societal engagement.…”
Section: Questionmentioning
confidence: 99%
“…The thesis has been criticised for emphasising science, technology and medicine and not covering the various disciplines of the humanities and social sciences (Albert, 2003;Godin, 1998). It has also been claimed that the thesis is poorly grounded in empirical research in individual disciplines and concrete university contexts (Ylijoki, 2003;Tuunainen, 2005aTuunainen, , 2005bYlijoki et al, 2011;Albert and McGuire, 2014). Inspired by these critiques, this article sets out to investigate the relation-…”
Section: Introductionmentioning
confidence: 99%
“…Outputs may range from publications (Bentley, Gulbrandsen, and Kyvik 2015) to practical applications such as patents as well as product and process innovations (Philpott et al 2011;Ylijoki, Lyytinen, and Marttila 2011). Academics focusing on Bohr research extend the knowledge base by publishing.…”
Section: Heterogeneity Emerging From Research Orientation: Bohr Pastmentioning
confidence: 99%